Experimental studies of ionic surfactant adsorption onto carbonate rocks. Issue 4 (16th February 2016) - Salari, Zargham; Ahmadi, Mohammad Ali
ABSTRACT: One of the main factors in chemical-based enhanced oil recovery, especially surfactant flooding, is a surfactant adsorption loss onto the reservoir rock. The main aim of this article is performing systematically a study on the adsorption behavior of an industrial ionic surfactant, which is currently employed in petroleum upstream. It is worth mentioning that sodium dodecyle sulphate was employed as an ionic surfactant in this study. Moreover, adsorption density at equilibrium condition was determined. Crushed carbonate rocks were used as rock samples. To determine adsorption behavior of the aforementioned surfactant onto carbonate surface, various surfactant concentrations were created in the range of 500 to 5, 000 ppm. Furthermore, via using an electrical conductivity measurement, the surfactant concentration in each solution before and after contacting with carbonate rocks was determined. Two well-known adsorption isotherms, including Freundlich and Langmuir, were employed to specify the adsorption mechanism. Based on the experimental results the Freundlich adsorption isotherm can predict the adsorption behavior of SDS onto carbonate rock surface.